DI-086 Interstitial lung disease induced by infliximab: a case report. (25th February 2017) - Pluchart, H; Chanoine, S; Beaumier, L; Quetant, S; Pison, C; Bedouch, P
Abstract : Background: Anti-TNFα drugs are immunosuppressive therapies prescribed in autoimmune diseases. Several clinical cases reported interstitial lung disease (ILD) onset with anti-TNFα drugs. 1 Purpose: In this clinical case we report ILD onset induced by infliximab in a patient with psoriasis. Material and methods: A literature review and a pharmacovigilance notification were done. The accountability of infliximab in ILD onset was estimated by the Naranjo adverse drug reaction probability scale. Results: The patient was a 57-year-old-man, treated for extensive psoriasis diagnosed in 1970. Our patient received eight medication therapies for psoriasis from 1987 to July 2014. He started therapy with infliximab 5 mg/kg in September 2015, on the following weeks: week 0, week 2, week 6, and then every 8 weeks (no pulmonary contraindication for infliximab for our patient). A significant improvement in skin condition was observed and the last injection of infliximab was in December 2015. In January 2016, our patient had a progressive dyspnoea onset (stage III according to the NYHA classification) 2 weeks after the last infliximab injection, leading to hospitalisation (decrease in vital capacity (VC) from 80% to 50–60%). ILD was shown on imaging, and bronchoalveolar fluid culture and immunological tests were negative. Cytology examinations found lymphocytic alveolitis (40%), supporting the hypothesis of hypersensitivity ILD. Lung function improved 1 month after infliximab cessation, without any medication (antibiotics or corticosteroids). The accountability of infliximab in ILD onset was probable according to Naranjo's score (score=7/13) In March 2016, VC was 77%, and in May 2016, there was a complete regression of pulmonary infiltration. Today, psoriasis is treated by secukinumab. Conclusion: Our case report suggests a role for infliximab in ILD onset. The link between ILD onset and anti-TNFα drugs remains unclear. Further research has to be conducted to elucidate the role of anti-TNFα agents in ILD onset or in worsening of pre-existing ILD, taking into account patients' interindividual variability. References and/or acknowledgements: 1. Curtis JR, et al. Incidence and complications of interstitial lung disease in users of tocilizumab, rituximab, abatacept and anti-tumour necrosis factor α agents, a retrospective cohort study. Arthritis Res Ther2015;17(1). No conflict of interest